ANALYSIS OF MORPHOLOGICAL AWARENESS IN READING COMPREHENSION - Iramona Juanisa; Deddy Suezdi (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
This research is analyzes morphological awareness in reading comprehension. The purpose of this research was to analyze the morphology of students' reading comprehension, to identify the types of morphological processes in reading comprehension and to describe the morphological processes in reading comprehension. The method is used in this research is qualitative method. During the current Pandemic, researchers decided to conduct research online through the Zoom application, this research was conducted by examining Jayabaya University students. There were 6 correspondents from the first semester students from several study programs to be given learning material and interviews. In this study, there are two types of instruments used, namely morphological tests and interviews. The way to obtain the results of this research is to analyze morphological awareness in reading comprehension using morphological test instruments and structured interviews. After being given an understanding of morphology, students can take a morphological awareness test in reading comprehension. The results of each student showed a fairly good percentage with the average score they got, namely 92.34.